Clinical Management and Outcome of Grade III Pneumonitis after Chemoradioimmunotherapy for Inoperable Stage III Non-Small Cell Lung Cancer—A Prospective Longitudinal Assessment - Diego Kauffmann-Guerrero; Julian Taugner; Chukwuka Eze; Lukas Käsmann; Minglun Li; Amanda Tufman; Farkhad Manapov (Diagnostics, 2021)
Background: Maintenance treatment with immune-checkpoint inhibition (ICI) has been shown to significantly improve patient prognosis after chemoradiotherapy (CRT) for inoperable stage III NSCLC. This survival advantage may be achieved at the expense of an increased probability for symptomatic pneumonitis as CRT as well as ICI treatment is associated with the risk of treatment-related pulmonary toxicity. Methods: We screened a prospective chemoradioimmunotherapy (CRT-IO) cohort consisting of 38 patients and identified patients with therapy-related grade 3 pneumonitis. All patients were treated with intravenous high dose corticosteroids and closely monitored by CT-scans and extended longitudinal lung function tests. We analyzed lung function parameters and CT morphological features to characterize patients’ outcome. Results: Six (16%) patients treated with CRT-IO developed grade 3 pneumonitis one to six months after completion CRT. In the CT imaging, pneumonitis was characterized by diffuse ground glass capacities and in part pulmonary consolidations within and outside the planning target volume. Onset of pneumonitis was accompanied by a reduction in diffusion capacity in all cases. The mean decline of diffusion capacity was 25.8% [6–53%]. Under treatment with corticosteroids, all patients recovered regarding symptoms and changes in CT morphology. In five out of six patients, diffusion capacity improved to at least 80% of the baseline [80–96%]. One patient showed a significant increase of diffusion capacity after treatment (from 32% to 53%) but reached only 62% of the initial value. Conclusions: Pneumonitis is a severe complication of CRT-IO. High-resolution CT imaging and extended lung function testing proved to be a suitable approach in detecting and monitoring of CRT-IO associated pneumonitis.